2017
DOI: 10.1016/j.chemosphere.2017.03.134
|View full text |Cite
|
Sign up to set email alerts
|

Modification of an existing in vitro method to predict relative bioavailable arsenic in soils

Abstract: The soil matrix can sequester arsenic (As) and reduces its exposure by soil ingestion. In vivo dosing studies and in vitro gastrointestinal (IVG) methods have been used to predict relative bioavailable (RBA) As. Originally, the Ohio State University (OSU-IVG) method predicted RBA As for soils exclusively from mining and smelting sites with a median of 5,636 mg As kg. The objectives of the current study were to (i) evaluate the ability of the OSU-IVG method to predict RBA As for As contaminated soils with a wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Though SBRC-GP assay was not the best based on our study (Li, Li, Cui, et al, 2015), based on two validation studies outside test soils, SBRC-GP assay was the best among the 5 in vitro assays as a surrogate for As-RBA in soils (Bradham et al, 2015). However, Whitacre et al (2017) reported that the SBRC-GP and IVG-GP assays were poor predictors of As-RBA for soils contaminated from gold mining activities, which were high in Fe concentrations. This leads to a modification of the IVG assay by including ascorbic acid, which is called California Bioaccessibility Method (Whitacre et al, 2017).…”
Section: Validation Of Ivivcs Using Independent Soilsmentioning
confidence: 72%
See 4 more Smart Citations
“…Though SBRC-GP assay was not the best based on our study (Li, Li, Cui, et al, 2015), based on two validation studies outside test soils, SBRC-GP assay was the best among the 5 in vitro assays as a surrogate for As-RBA in soils (Bradham et al, 2015). However, Whitacre et al (2017) reported that the SBRC-GP and IVG-GP assays were poor predictors of As-RBA for soils contaminated from gold mining activities, which were high in Fe concentrations. This leads to a modification of the IVG assay by including ascorbic acid, which is called California Bioaccessibility Method (Whitacre et al, 2017).…”
Section: Validation Of Ivivcs Using Independent Soilsmentioning
confidence: 72%
“…However, Whitacre et al (2017) reported that the SBRC-GP and IVG-GP assays were poor predictors of As-RBA for soils contaminated from gold mining activities, which were high in Fe concentrations. This leads to a modification of the IVG assay by including ascorbic acid, which is called California Bioaccessibility Method (Whitacre et al, 2017).…”
Section: Validation Of Ivivcs Using Independent Soilsmentioning
confidence: 99%
See 3 more Smart Citations